Paranasal sinus fungus ball: analysis of clinical characteristics and surgical outcomes - Pınar, Ercan; İmre, Abdulkadir and Ata Ece, Ahmet and Aladağ, İbrahim and Aslan, Hale and Özkul, Yılmaz and Dinçer, Elif (ENT Updates, 2015)
Objective: The aim of the present study was to analyse the clinical, radiographic, and surgical outcomes of paranasal fungus ball. Methods: A retrospective data analysis was performed on 16 patients who underwent endoscopic sinus surgery for paranasal sinus fungus ball between December 2005 and November 2014. The patient’s demographic data, clinical presentations, radiological findings and surgical outcomes were analysed. Results: There were 10 female (62.5%) and six male (37.5%) patients with a mean age of 53.6 (range: 32 to 74) years. Most common symptoms were headache and facial pain. Computed tomography showed a hyper-dense area in 12 patients (75%) and sclerosis in bony walls of the sinus in 13 patients (81.3%). Magnetic resonance imaging revealed a marked low intensity on T2 weighted images in all cases (100%). All patients were treated with functional endoscopic sinus surgery. Only one patient had a recurrence in the postoperative period. Conclusion: The surgical opening of affected sinus ostium and removal of the fungal concentration were the treatment of choice in all cases.